2019
DOI: 10.1177/1086296x18820659
|View full text |Cite
|
Sign up to set email alerts
|

Representations of Autism in Online Harry Potter Fanfiction

Abstract: From literary canons all the way to the motion picture industry, the artistic and popular cultural experience of marginalized or nonmainstream groups has been one of being represented by the other. In this article, we explore how online fanfiction, as an audience-driven, interactive form of writing, may offer a way for members of nonmainstream groups to push back against and offer alternatives to stereotypical and normative discourses. We focus on how autistic people, family members, teachers, and advocates ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Results show that portrayals of autism can increase social awareness of autism (Nordahl-Hansen, 2017a), as well as break with the most common autism stereotypes (Lugo et al, 2017;Black et al, 2019).…”
Section: Benefits and Downsidesmentioning
confidence: 99%
“…Results show that portrayals of autism can increase social awareness of autism (Nordahl-Hansen, 2017a), as well as break with the most common autism stereotypes (Lugo et al, 2017;Black et al, 2019).…”
Section: Benefits and Downsidesmentioning
confidence: 99%
“…Furthermore, it has been shown that online pop culture fandom communities and affinity spaces have helped historically marginalized students engage in literacy learning (Black, 2005(Black, , 2009Black et al, 2019;Williamson et al, 2020). These studies identified hybridity, intertextuality, representation, and a nurturing culture as features that facilitate learning that the inschool space does not always offer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, such discourses—especially in the wake of identity politics and recognition of the social model of disability—are increasingly challenged from a neurodiversity perspective, and by the accounts of autistic young people and adults (Grinker, 2020; Leadbitter et al, 2021). Nevertheless, popular culture still contains ‘reductive representations’ of autistic people (Black et al, 2019, p. 31), and accounts drawing on the voices of well‐known autistic people tend to focus more on their adaptive success, not that of wider society (Mullen, 2015).…”
Section: Autism Stigma and Powermentioning
confidence: 99%